2015
DOI: 10.1259/dmfr.20140323
|View full text |Cite
|
Sign up to set email alerts
|

The skeletal maturation status estimated by statistical shape analysis: axial images of Japanese cervical vertebra

Abstract: Objectives: To evaluate axial cervical vertebral (ACV) shape quantitatively and to build a prediction model for skeletal maturation level using statistical shape analysis for Japanese individuals. Methods: The sample included 24 female and 19 male patients with hand-wrist radiographs and CBCT images. Through generalized Procrustes analysis and principal components (PCs) analysis, the meaningful PCs were extracted from each ACV shape and analysed for the estimation regression model. Results: Each ACV shape had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Landmarks(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) on the left-hand radiography used in this study were shown.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Landmarks(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) on the left-hand radiography used in this study were shown.…”
mentioning
confidence: 86%
“…A significant innovation in analysing skeletal maturation is concerned with the way in which shape and size are characterised [5,6]. New methodologies and concepts, which are known collectively as geometric morphometrics, are being increasingly used in evolutionary contexts, since they make it possible to distinguish between a component of size change over time (growth) and one of shape change over time (development).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation